CARTHAGE AND ROME, THE THEORY AND METHODOLOGY OF INTERDISCIPLINARY RESEARCH INSTITUTIONS NEGOTIABILITY AND LEGITIMATE POWER UNDER ECONOMIC DEVELOPMENT: HISTORY, POLITICS, ECONOMICS - Malyshev, I.A. (Perm Federal Research Centre Journal, 2016)
The purpose of this research was to identify the reasons for low competitiveness of the Russian economy. The key subsystems having crucial influence on the competitiveness of the country, as well as the region, were determined: political, economic, scientific, technological, innovative, social, infrastructural, law and management. The main causes were identified: dysfunction of political and social institutions, lack of accountability, the low level of negotiability of the present political elite.